Pengembangan Sistem Informasi Profil Sekolah Pada SDN Wailiti Berbasis Web Menggunakan Metode Waterfall - Seru Jira, Didakus; Yustina Yuliana Sugo; Magdalena Hogar; Gregorius Tega Nitit; Gabriel Novi Elias Fernande (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
SD Negeri Wailiti is an institution engaged in education located in Maumere City, Sikka Regency, East Nusa Tenggara Province, Indonesia. In carrying out its operational activities, SD Negeri Wailiti requires an effective and efficient information system to manage the school profile. School profile is the school's data that includes name, history, vision and mission, founder, address, city, contact number as well as school facilities and all forms of activities held by the school. Some of these data need to be packaged in a permanent online facility or media so that in the future it can be used. From the data obtained, it is said that the system used by SDN Wailiti is still oral, namely socialisation in the surrounding community and through information boards or brochures. The purpose of this research is to develop a web-based school profile information system at SD Negeri Wailiti using the waterfall method because this method is the most suitable development model used by developers, system project work is easy to control and can be on time. The programming language that the author uses is PHP (Hypertext Preprocessor) and uses MySQL database. This information system can be used by the school to improve the quality of information services to the community. Testing the feasibility of the system using blackbox testing.